2012
DOI: 10.1007/s00259-011-2053-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative methods for PET image segmentation in pharyngolaryngeal squamous cell carcinoma

Abstract: Purpose Several methods have been proposed for the segmentation of 18 F-FDG uptake in PET. In this study, we assessed the performance of four categories of 18 F-FDG PET image segmentation techniques in pharyngolaryngeal squamous cell carcinoma using clinical studies where the surgical specimen served as the benchmark. Methods Nine PET image segmentation techniques were compared including: five thresholding methods; the level set technique (active contour); the stochastic expectationmaximization approach; fuzzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 33 publications
0
72
1
Order By: Relevance
“…Our results turns to be competitive with those reported in [3], where a set of segmentation techniques are compared in terms of SOI using a dataset of 7 patients suffering from pharyngolaryngeal squamous cell carcinoma. In particular, in [3] it is found that one of the best performing method, termed FCM-SW, yields an average SOI of 0.54.…”
Section: Experimental Validationcontrasting
confidence: 46%
See 3 more Smart Citations
“…Our results turns to be competitive with those reported in [3], where a set of segmentation techniques are compared in terms of SOI using a dataset of 7 patients suffering from pharyngolaryngeal squamous cell carcinoma. In particular, in [3] it is found that one of the best performing method, termed FCM-SW, yields an average SOI of 0.54.…”
Section: Experimental Validationcontrasting
confidence: 46%
“…However, PET segmentation remains an open problem mainly because of the limited image resolution and presence of acquisition noise [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,31,[72][73][74]76,80 However, few groups have validated delineation process using different imaging modalities against surgical resection specimens. 31,[81][82][83][84][85] In general, all imaging modalities overestimated the tumour extension compared with surgical specimen. Nevertheless, none of the image modalities (CT, MRI or PET) completely encompassed the surgical specimen volume because of an underestimation of superficial tumour extension in the mucosa, 31 as also reported by Ng et al 81 According to Daisne et al, 31 the GTV delineated from 18 F-FDG-PET applying an adaptive signal-to-background method was significantly smaller than GTV delineated by CT or MRI.…”
Section: Radiotherapy Planningmentioning
confidence: 99%